LIMITATIONS AND OPPORTUNITIES FOR FUNDING AGRICULTURE AND RURAL DEVELOPMENT IN THE REPUBLIC OF SERBIA - Ristić, Lela; Todorović, Violeta; Jakšić, Milena (Economics of Agriculture, 2018)
Funding is one of the most important issues of agriculture and rural development of the Republic of Serbia, because insufficient financial resources allocated to this sector of the countrys economy are considered the key limitation for better valorization of agricultural resources and the revitalization of rural areas. Agribusiness and rural development have a major socio-economic importance for the Republic of Serbia, which is supported by a number of strategic documents, development indicators and scientific and expert analysis implemented in the country and at a global level; therefore, the aim of this study is to determine whether it is necessary and possible to improve the funding of agricultural development and rural economy of the Republic of Serbia, in current conditions. The survey results indicate potential sources, i.e., the possible ways of funding agriculture and non-agricultural activities in the rural areas of the Republic of Serbia.